2023
DOI: 10.1186/s43014-023-00138-z
|View full text |Cite
|
Sign up to set email alerts
|

A review on biochemical constituents of pumpkin and their role as pharma foods; a key strategy to improve health in post COVID 19 period

Abstract: Progression of today’s world has been given setback due to the adversity of a novel, viral, deadly outbreak COVID 19, which raised the concerns of the scientists, researchers and health related officials about the inherent and adaptive immune system of the living body and its relation with healthy diet balanced with pharma foods. Now world is coming out of the destructive pandemic era, the choice of right food can help to build and boost adaptive immunity and pumpkin due to excellent profile of functional and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(4 citation statements)
references
References 94 publications
(90 reference statements)
0
4
0
Order By: Relevance
“…Lemongrass extracts, when applied to animals, exhibited hypoglycemic and hypolipidemic activities, which might be attributed to the bioactive components present in this medicinal herb. 6 Boeira et al 17 extracted bioactive components from lemongrass and incorporated them in meat products to check their antimicrobial and antioxidant activities. They stated that phenolics and flavonoids are the major bioactive compounds responsible for such medicinal properties.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Lemongrass extracts, when applied to animals, exhibited hypoglycemic and hypolipidemic activities, which might be attributed to the bioactive components present in this medicinal herb. 6 Boeira et al 17 extracted bioactive components from lemongrass and incorporated them in meat products to check their antimicrobial and antioxidant activities. They stated that phenolics and flavonoids are the major bioactive compounds responsible for such medicinal properties.…”
Section: Discussionmentioning
confidence: 99%
“…16 Due to their qualities as anticancer, antiviral, calming, anti-microbial, as well as, allopathic properties, phenolics and flavonoids are two types of polyphenols present in lemongrass, which have exhibited antioxidant and antimicrobial behavior in chicken sausages. 17 As the world emerges from the destructive pandemic period, eating the right foods can help to develop and strengthen adaptive immunity. Plant-based foods, due to the presence of functional and nutraceutical components, are a useful part of a daily diet.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies in DNCB-induced mouse models have demonstrated that purslane lowers serum IgE, mast cell levels, and histamine skin concentration, potentially through its targeting of IFN-γ, TNFα, and IL-4 [67]. Pumpkin pulp is rich in β-carotene, fatty acids, moisture, and flavonoids and has proven that it can be used for many skin disorders such as dermatitis, and that it can be given orally or topically [68]. Application of pumpkin pulp extract as an ointment improved AD patient DLQI scores within four weeks [69].…”
Section: Plant Extracts and Phytochemicals With Immunomodulatory Effe...mentioning
confidence: 99%